2021
DOI: 10.5194/wes-2021-57
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying wind plant blockage under stable atmospheric conditions

Abstract: Abstract. Wind plant blockage reduces the wind velocity upstream undermining turbine performance for the first row of the plant. We assess how atmospheric stability modifies the induction zone of a wind plant in flat terrain. We also explore different approaches to quantifying the magnitude and extent of the induction zone from field-like observations. To investigate the influence from atmospheric stability, we compare simulations of two stable boundary layers using the Weather Research and Forecasting model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The stable-boundary-layer simulation closely follows the configuration of Sanchez Gomez et al (2021). The surface condition for the stable case is driven with a cooling rate, rather than a negative heat flux (Basu et al, 2007).…”
Section: Idealized Atmospheric Boundary Layer Simulations Of Varying ...mentioning
confidence: 81%
“…The stable-boundary-layer simulation closely follows the configuration of Sanchez Gomez et al (2021). The surface condition for the stable case is driven with a cooling rate, rather than a negative heat flux (Basu et al, 2007).…”
Section: Idealized Atmospheric Boundary Layer Simulations Of Varying ...mentioning
confidence: 81%
“…We briefly digress from the discussion on wakes to note that upwind blockage (Schneemann et al, 2021;Sanchez Gomez et al, 2021) can be observed in these idealized simulations and tangential flow accelerations, similar to the speed-ups seen by Nygaard and Hansen (2016), can be observed adjacent to the wakes. Blockage is strongest in the stable conditions, where 0.125-0.250 m s −1 deficits extend 5 km-7 km upwind of the plant.…”
Section: Hub-height Wind Speed Deficitsmentioning
confidence: 84%
“…We briefly digress from the discussion on wakes to discuss two effects that are secondary to the primary analysis of this study: upwind blockage and flow acceleration. Upwind blockage (Schneemann et al, 2021;Sanchez Gomez et al, 2021) occurs in some of the idealized simulations. Blockage is strongest in the stable conditions, where 0.5 m s −1 deficits extend 5-10 km upwind of the plant.…”
Section: Hub-height Wind Speed Deficitsmentioning
confidence: 99%